1990
DOI: 10.1021/bi00471a018
|View full text |Cite
|
Sign up to set email alerts
|

Structural perturbation of the a3-CuB site in mitochondrial cytochrome c oxidase by alcohol solvents

Abstract: Ethanol has been observed to cause a perturbation of the catalytic center of the major respiratory protein cytochrome c oxidase. These effects were examined by Fourier transform infrared spectroscopy of carbon monoxide complexes of cytochrome a3Fe and of CuB formed by low-temperature photodissociation of the a3FeCO complex. Carbon monoxide binds to reduced cytochrome oxidase in two major structural forms, alpha and beta, both of which are altered by ethanol. In the absence of ethanol, 15-22% of the total cytoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…56, 57 Cytochrome c oxidase (CcO) is the terminal respiratory enzyme in the mitochondrial electron transfer chain responsible for reduction of molecular oxygen to water. In strongly visible light, CO is dissociated from the heme a3 pocket and rebinds to the Cu B with at least two CO stretching frequencies between 2060 cm −1 and 2035 cm −1 .…”
Section: Discussionmentioning
confidence: 99%
“…56, 57 Cytochrome c oxidase (CcO) is the terminal respiratory enzyme in the mitochondrial electron transfer chain responsible for reduction of molecular oxygen to water. In strongly visible light, CO is dissociated from the heme a3 pocket and rebinds to the Cu B with at least two CO stretching frequencies between 2060 cm −1 and 2035 cm −1 .…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of the α and β-forms of the CO-complex of C c O was first made by Alben and coworkers in low temperature photolysis studies of bovine mitochondria with FTIR [18, 24-26]. The presence of the two conformers of C c O was later confirmed in several different preparations of mammalian oxidases, including rat heart myocytes and opossum heart tissue slices [24].…”
Section: Discussionmentioning
confidence: 99%
“…In one of the earliest studies, Lieber and co-workers (20) showed that alcohol treat-ment in baboons resulted in markedly altered hepatic mitochondrial CcO activity. Similarly, exposure of mitochondrial membrane fractions with alcohol caused the structural perturbation of the a3-CuB site, affecting CcO activity (21). Another study showed that hepatic mitochondrial NO levels markedly increased under chronic alcohol treatment (22,23), which covalently modified the heme moiety leading to reduced CcO activity.…”
mentioning
confidence: 99%